2016
DOI: 10.1016/j.nut.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of breakfast omission on subjective appetite, metabolism, acylated ghrelin and GLP-17-36 during rest and exercise

Abstract: Please cite this article as: Clayton DJ, Stensel DJ, James LJ, Effect of breakfast omission on subjective appetite, metabolism, acylated ghrelin and GLP-1 7-36 during rest and exercise, Nutrition (2015), doi: 10.1016/j.nut.2015.06.013. This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…Additionally, this study found that the glycaemic response to a standardised lunch was attenuated in habitual breakfast omitters, suggesting some metabolic adaptation may occur over time. In a similar study, Clayton et al (29) found no difference in acylated ghrelin or GLP-1 concentrations either 1·5 or 3·5 h after a standardised lunch. Collectively, these studies suggest breakfast minimally affects the orexigenic appetite hormone ghrelin, with some evidence that breakfast may increases anorexigenic hormone profiles, in response to subsequent standardised feeding.…”
Section: Effect Of Breakfast On Peripheral Appetite Hormonesmentioning
confidence: 85%
See 3 more Smart Citations
“…Additionally, this study found that the glycaemic response to a standardised lunch was attenuated in habitual breakfast omitters, suggesting some metabolic adaptation may occur over time. In a similar study, Clayton et al (29) found no difference in acylated ghrelin or GLP-1 concentrations either 1·5 or 3·5 h after a standardised lunch. Collectively, these studies suggest breakfast minimally affects the orexigenic appetite hormone ghrelin, with some evidence that breakfast may increases anorexigenic hormone profiles, in response to subsequent standardised feeding.…”
Section: Effect Of Breakfast On Peripheral Appetite Hormonesmentioning
confidence: 85%
“…However, it is interesting to note that the subjective appetite response to subsequent meals appears to be unaffected by prior omission of breakfast, suggesting that consumption of breakfast only provides a transient suppression of appetite (23,24,(26)(27)(28)(29) . This was recently investigated in two studies that were designed to determine how 24 h subjective appetite profiles responded to breakfast consumption or omission, with ad libitum (28) or standardised (29) lunch and dinner meals. In these studies, breakfast (25 % estimated energy requirements) was consumed at 08·00 hours, with lunch and dinner meals consumed at 12·30 and 18·00-19·00 hours.…”
Section: Effect Of Breakfast On Subjective Appetitementioning
confidence: 99%
See 2 more Smart Citations
“…Following an overnight fast, hunger is elevated, with consumption of breakfast suppressing hunger (18)(19)(20) , an effect that may be regulated by hormones involved in appetite regulation. Whether such appetite effects play a role in any performance responses to pre-exercise feeding is unknown, since most studies have not measured the two in combination, but Naharudin et al (16) reported that the increased resistance exercise performance following breakfast occurred concurrently with a suppression in hunger.…”
mentioning
confidence: 99%